The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/mop.32810
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aluminum alloy by laser‐induced breakdown spectroscopy combined with machine algorithm

Abstract: Discarded aluminum alloys are a form of recyclable metal materials, and their classification and identification are highly important. In this work, laser‐induced breakdown spectroscopy (LIBS) technique combined with principal component analysis (PCA) and least‐squares support‐vector machine (LSSVM) algorithm were used to classify and identify five types of aluminum alloys. Exploratory analysis of five types of aluminum alloys by PCA was performed to achieve better segregation. The identification accuracy of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Dai et al 16 identified aluminum alloy by LIBS combined with machine algorithm. Sirven et al 17 used LIBS combined with neural networks to perform qualitative and quantitative analysis of chromium-contaminated soil. Wang et al 18 used external and internal standard methods, and multiple linear regression to quantitatively analyze Pb in tea.…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al 16 identified aluminum alloy by LIBS combined with machine algorithm. Sirven et al 17 used LIBS combined with neural networks to perform qualitative and quantitative analysis of chromium-contaminated soil. Wang et al 18 used external and internal standard methods, and multiple linear regression to quantitatively analyze Pb in tea.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used in qualitative elemental analysis. 7,8 However, its reliability is relevant to the laser properties, substrates, and ambient surroundings. 9 Furthermore, it is important to measure accurate temperature for improving the application of LIBS.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning applied to LIBS data from aluminium alloys has been reported in other papers. 46,47 The paper by Dai et al identied different aluminium alloys (060, 6061, 5052, 2024, and 7075) with the prospect of re-cycling them from scrap. 47 The authors rst used PCA to help with the identication and then followed this by least squares support vector machine to classify ve different aluminium alloys.…”
Section: Copper and Copper-based Alloysmentioning
confidence: 99%
“…46,47 The paper by Dai et al identied different aluminium alloys (060, 6061, 5052, 2024, and 7075) with the prospect of re-cycling them from scrap. 47 The authors rst used PCA to help with the identication and then followed this by least squares support vector machine to classify ve different aluminium alloys. The results were compared with those obtained from data analysis using support vector machine alone.…”
Section: Copper and Copper-based Alloysmentioning
confidence: 99%